Over my dead body eaudiobook - Archer, Jeffrey (Detective William Warwick, 2021)
The gripping new instalment in the William Warwick series, An Eye for an Eye, is available to pre-order now! The New York Times bestselling novel – an unputdownable story of murder, revenge and betrayal from international number one bestseller Jeffrey Archer. THE CLOCK IS TICKING IN THIS ROLLERCOASTER RIDE OF A THRILLER... In London, the Metropolitan Police set up a new Unsolved Murders Unit—a cold case squad—to catch the criminals nobody else can. In Geneva, millionaire art collector Miles Faulkner—convicted of forgery and theft—was pronounced dead two months ago. So why is his unscrupulous lawyer still representing a dead client? On a luxury liner en route to New York, the battle for power within of a wealthy dynasty is about to turn to murder. And at the heart of all three investigations are Detective Chief Inspector William Warwick, rising star of the department, and ex-undercover agent Ross Hogan, brought in from the cold. But can they catch the killers before it's too late? Praise for Jeffrey Archer: "Archer is a master entertainer." —Time "Cunning plots, silken style...Archer plays a cat-and-mouse game with the reader." —The New York Times "One of the top ten storytellers in the world." —Los Angeles Times "A storyteller in the class of Alexandre Dumas." —The Washington Post Over My Dead Body was a New York Times bestseller November 7th 2021.